Assessment of knowledge and awareness of monkeypox viral infection in Palestine: a community-based study - El Sharif, Nuha; Ahmead, Muna (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundMonkeypox (MPXV) is a re-emerging global health threat, particularly in non-endemic areas such as Palestine, where research is scarce. This study aims to assess public knowledge and awareness of MPXV in PalestineMethodsA 38-item questionnaire assessed socioeconomic status, health status, and MPXV knowledge among 1241 participants. Pearson’s Chi-square test examined the association between high and low knowledge levels and explanatory variables. A logistic regression model examined the relationships between knowledge levels and the explanatory factors of the investigation.ResultsThe study indicated that merely 23% of the 1241 participants exhibited a high level of knowledge regarding monkeypox. Approximately 20% of the participants felt that the virus might be transmitted through contaminated surfaces, whereas 40% acknowledged close contact with infected individuals as a mode of transmission. Furthermore, 11.4% of the participants accurately identified an incubation period of 5 to 21 days. Concerning symptoms, 50% identified rash and high fever as the most severe, whereas 25% reported fatigue, muscle pain, swollen lymph nodes, and breathing issues. Regarding prevention and treatment, 38% asserted that masks may not prevent MPXV, 31% claimed that no treatment is available, and 50% believed that immunization can be effective. Knowledge was significantly higher among those with more educational attainment and healthcare employment (p-value< 0.05). The primary sources of information were friends, family, and social media.ConclusionThe understanding of monkeypox infection among the Palestinian population was found to be somewhat insufficient. These findings highlight the urgent need for public education on monkeypox to increase awareness and engage the public prior to any potential future outbreak.